Impact of Parental Bonding on Body Dissatisfaction: The mediating Effect of Socio-cultural Attitude towards Appearance among University Students - Arshad, Bushra; Khaliq, Aqsa Abdul; Haroon, Mehak (Annals of Human and Social Sciences, 2024)
This study was intended to analyze the impact and relationship of parental bonding on body dissatisfaction by the mediating role of socio-cultural attitude towards appearance among university students. Body appearance has become a great concern among university students and it can negatively impact an individual. University students are an important asset for any nation and it becomes vital to understand the variables that may affect their lives. The total sample was 325 that was selected by per indication method by multiply the total items (65) of all scales to 5. 165 were males and 158 were females was obtained through Convenient sampling technique. Age range of the sample size was 18 years above. The instruments used to collect the data were Parental Bonding scale (Parker et al.,1979) 25- items. It has two subscales, care and overprotection. Body dissatisfaction scale (Garner et al.,1983) includes 10 items and Socio-cultural attitude towards appearance scale Thompson et al., (2004) contains 30 items that were divided into 4 subscales as information, Pressures, Internalization general and Internalization Athlete. Findings indicated that there is impact of parental bonding on body dissatisfaction. The socio-cultural attitude towards appearance played a moderator role between parental bonding and body dissatisfaction rather than mediator.